Distinct myeloid cell subpopulations in controlling systemic candidiasis - Teo, Yi Juan (2018)
Systemic Candidiasis is one of the most frequent nosocomial infections to date, with a mortality rate as high as 40%. Despite continual efforts in antifungal therapy and hygienic measures in hospitals, the incidence of such invasive infection escalates, owing to the expanding population of immunocompromised patients and the increasing resistance against common antifungal chemotherapeutics. Over the past decades, host immunity against systemic candidiasis has been the focus of numerous studies with an aim to explore potential cure and in search of effective vaccine candidates. Although the importance of neutrophils in this infection is well-established, the role of mononuclear phagocytic subsets, which includes DCs and macrophages, during invasive Candida infection, is still unclear due to the lack of appropriate tools to specifically ablate these individual mononuclear phagocytic cell subpopulations. To this end, we exploited four different in house-generated Diphtheria Toxin Receptor (DTR) transgenic mouse strains to study the roles of CD8+/CD103+ DCs (Clec9A-DTR), CD11b+ DCs (Clec4a4-DTR), pDCs (Siglec H-DTR) and CD169+ macrophages (CD169-DTR) in the host immunity against disseminated candidiasis, in which depletion of target cell populations in vivo can be achieved upon DT injection. Noteworthy, we consistently detected highest and persisting fungal load in the kidneys, as compared to the other vital organs in our murine model of systemic candidiasis using Candida albicans SC5314 strain, indicating that kidney is the main target organ. Here, we reiterated the pivotal role of neutrophils in the host defense against invasive Candida infection, where ablation of neutrophils in vivo caused rapid death of the mice as soon as 2 days post infection. Correspondingly, these mice displayed significantly higher fungal burden in the kidneys when compared to the control mice. Next, our data demonstrated that individual DC subset (CD8+/CD103+ DCs, CD11b+ DCs and pDCs) is dispensable for the host immunity against invasive Candida infection, in which mice depleted either of these DC subsets displayed similar mortality, susceptibility and organ fungal burdens as that of the infected controls. In the subsequent part of our experiments, we showed that kidney CD169+F480+ macrophages are absolutely required for the host defense against systemic candidiasis. CD169DTR mice consistently exhibited higher susceptibility and their kidney fungal burden was significantly higher at the later stage of infection when compared to the control mice. In addition, kidneys of CD169-DTR mice appeared to be more damaged and inflamed than the control kidneys, as evidenced by the kidney histology and higher expression of KIM-1, endothelial adhesion molecules, pro-inflammatory cytokines and chemokines. Interestingly, based on our kidney histological observations, the absence of CD169+ macrophages seemed to adversely influence the neutrophils candidacidal capacity. Further investigations are warranted to unravel the mechanisms behind the modulation of Candida immunity by CD169+ macrophages. Our data suggest that these macrophages may likely be involved in restraining inflammation or in potentiating neutrophils candidacidal abilities during systemic candidiasis.